Anti‐C1q autoantibodies are linked to autoimmune thyroid disorders in pregnant women. (12th August 2016) - Vitkova, H.; Jiskra, J.; Springer, D.; Limanova, Z.; Telicka, Z.; Bartakova, J.; Trendelenburg, M.; Potlukova, E.
Summary: Anti‐C1q antibodies (anti‐C1q) have been implicated in the pathogenesis of autoimmune diseases, including autoimmune thyroid disorders (AITD). The aim of this study was to evaluate the association between anti‐C1q and thyroid function in pregnancy‐associated AITD. In 96 pregnant women screened positive for AITD (thyroid dysfunction and/or antibodies against thyroperoxidase – TPOAb), anti‐C1q were measured during the 9‐11th gestational week and after delivery (median 16 months after delivery), and compared to the corresponding serum levels of thyroid hormones. As controls, 80 healthy pregnant women, 72 non‐pregnant AITD patients and 72 blood donors were included. In the non‐pregnant AITD group, two serum samples ≥ 6 months apart were analysed. Compared to blood donors, anti‐C1q levels were substantially higher in all pregnant women analysed. In pregnancy, anti‐C1q levels were higher in the TPOAb‐positive women than in controls (37 versus 17·5%, P  < 0·0001). Anti‐C1q‐positive pregnant women screened positive for AITD had higher thyroid‐stimulating hormone (TSH) levels than anti‐C1q‐negative women (2·41 versus 1·94 mU/l, P =  0·01), and TSH correlated positively with anti‐C1q ( r  = 0·226, P  = 0·045) in the TPOAb‐positive women. After delivery, serum levels of anti‐C1q decreased in the positively screened TPOAb‐negative women (8·8 versus 5·9 U/l, P  = 0·002), but not in the TPOAb‐positive ones, and they no longer correlated with TSH. Anti‐C1q antibody levels increase during pregnancy in general and even more in the context of AITD, where they correlate with thyroid stimulating hormone levels.